2020
DOI: 10.1212/wnl.0000000000009240
|View full text |Cite
|
Sign up to set email alerts
|

Total Aβ 42 /Aβ 40 ratio in plasma predicts amyloid-PET status, independent of clinical AD diagnosis

Abstract: ObjectiveTo explore whether the plasma total β-amyloid (Aβ) Aβ 42 /Aβ 40 ratio is a reliable predictor of the amyloid-PET status by exploring the association between these 2 variables in a subset of the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 38 publications
13
95
1
1
Order By: Relevance
“…In comparison, prescreening of CN participants solely based on age and APOE-ε4 genotype would reduce the number of necessary PET scans by only 40%. Previous studies using IP-MS [36] or ABtest ELISAs [14,15] to quantify the plasma amyloid ratio reported higher PPVs than the ones observed here, which might give the impression that these methods are superior to the SIMOA or conventional ELISA technology. However, the prevalence of amyloid-PET positivity was also higher in these other studies (≈ 30%), which directly influences the reported PPV.…”
Section: Discussioncontrasting
confidence: 64%
“…In comparison, prescreening of CN participants solely based on age and APOE-ε4 genotype would reduce the number of necessary PET scans by only 40%. Previous studies using IP-MS [36] or ABtest ELISAs [14,15] to quantify the plasma amyloid ratio reported higher PPVs than the ones observed here, which might give the impression that these methods are superior to the SIMOA or conventional ELISA technology. However, the prevalence of amyloid-PET positivity was also higher in these other studies (≈ 30%), which directly influences the reported PPV.…”
Section: Discussioncontrasting
confidence: 64%
“…As A self-assembly strongly depends on the context of its release, we sought to determine whether the assembly of interest was produced particularly by CHO cells or commonly across other models. This reduction correlated with the severity of AD symptoms exerted by the patients (see raw values in Table1), concordantly with previous reports [51]. On the contrary, relative quantification of hexameric A levels detected by Western blotting, using soluble APP as an intrasubject control, revealed an increase in hexameric levels with the progression of AD (Table1).…”
Section: Formation Of Hexameric A Across a Wide Range Of Modelssupporting
confidence: 91%
“…The abnormal threshold for the ratio of plasma Aβ in AIBL participants was set as ˂0.085. This threshold was based upon receiver operating characteristics using the Youden index for plasma Aβ against brain Aβ positives and negatives ( Doecke et al , 2020 ).…”
Section: Methodsmentioning
confidence: 99%